Research on Architectural Art and Sustainable Design of Ginling College Historic District (Nanjing, China) - Hechi Wang; Zhaoyi Yan; Xinyi He; Yingqiu Song; Yanyan Huang; Junxue Zhang; Qi Zhou; Zerong Yan; Xinran Jiang (Buildings, 2023)
Ginling College is the first women’s college founded by the American Christian Church in Nanjing, China, in the early 20th century. The architectural style of the school reflects the orientation of the “Chinese localization” of the Christian Church at that time. It is a representative work of the revival of traditional Chinese architecture. It is known as a “Renaissance of Chinese traditional architecture” and profoundly influenced later generations. Due to its important historical status and artistic value, the Ginling College complex has been designated by the Chinese government as a national key cultural relic protection unit and China’s 20th-century architectural heritage, and the protection scope of the Ginling College historical district has been specially designated for overall protection. Currently, little research has been conducted on this historic area, so the authors undertook this project. This paper adopts a combination of qualitative and quantitative methods for research, starting from the two aspects of architectural art and sustainable design, and analyzes in detail the artistic characteristics of the project, the structural materials obtained locally, and the sustainable design method that utilizes natural lighting and ventilation to explore a modern campus design method based on the concept of sustainable design with a “combination of Chinese and Western architectural art”. Through artistic creation and technological innovation, traditional Chinese revival architecture has realized a harmonious coexistence between man and nature, embodying the design concept of sustainable development, and promoting the development of architecture and the region.